Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(B=\frac{2\left(x^2-4x+5\right)}{\left(x+1\right)^2\left(x-3\right)}\)
ĐKXĐ: \(x\ne-1;3\)
\(A=\frac{\left(x+1\right)^2}{\left(x-2\right)^2+1}\ge0\) do \(\left\{{}\begin{matrix}\left(x+1\right)^2\ge0\\\left(x-2\right)^2+1>0\end{matrix}\right.\) \(\forall x\)
\(\Rightarrow A_{min}=0\) khi \(x=-1\)
Để AB>0 \(\Leftrightarrow\left\{{}\begin{matrix}A\ne0\\B>0\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}x\ne-1\\\frac{2\left[\left(x-2\right)^2+1\right]}{\left(x+1\right)^2\left(x-3\right)}>0\end{matrix}\right.\) \(\Rightarrow x-3>0\Rightarrow x>3\)
a. ĐK \(\hept{\begin{cases}x\ne0\\x+5\ne0\end{cases}\Rightarrow\hept{\begin{cases}x\ne0\\x\ne-5\end{cases}}}\)
b. \(A=\frac{x^2+2x}{2x\left(x+5\right)}+\frac{x-5}{x}+\frac{50-5x}{2x\left(x+5\right)}=\frac{x\left(x^2+2x\right)+2\left(x-5\right)\left(x+5\right)+50-5x}{2x\left(x+5\right)}\)
\(=\frac{x^3+2x^2+2x^2-50+50-5x}{2x\left(x+5\right)}=\frac{x^3+4x^2-5x}{2x\left(x+5\right)}\)
\(=\frac{x\left(x+5\right)\left(x-1\right)}{2x\left(x+5\right)}=\frac{x-1}{2}\)
Để \(A=1\Rightarrow\frac{x-1}{2}=1\Rightarrow x=3\)
Để \(A=-3\Rightarrow\frac{x-1}{2}=-3\Rightarrow x=-5\)
Vậy với x=3 thì A=1 ; với x=-5 thì A=-3
\(\text{để B có nghĩa }\Rightarrow x^3-x^2-5x-3\ne0\)
ta có: \(x^3-x^2-5x-3\)
\(=x^3+2x-3x^2-5x+x-3\)
\(=\left(x-3\right).\left(x^2+2x\right)+1.\left(x-3\right).\)
\(=\left(x-3\right).\left(x+1\right)^2\Rightarrow x\ne3\text{ và }x\ne-1\)